DESAIN MOZAIK PADA BINGKAI JAJARAN GENJANG DENGAN MOTIF GEOMETRIS - Sakinah, Zulfatus; Juliyanto, Bagus; Ubaidillah, Firdaus (Jurusan Matematika FMIPA Universitas Jember, 2021)
This research is intended to obtain the steps of a parallelogram frame mosaic design with a Pinwheel tile pattern with geometric motifs. The design of the basic shape of the mosaic on the interior of a parallelogram which is then filled with several geometric motifs in the basic shape of the mosaic is the method used in this study. The results obtained from this study are the basic modeling procedure for the mosaic with a parallelogram frame. the first step, setting the second repetition (iteration) pinwheel tile. the second step, dividing the field on the frame into several basic shapes of mosaics. then for the procedure for filling the basic shape of the geometric patterned mosaic with the following steps. First, determine the geometric motifs that match the selected mosaic shapes. Secondly, fill the motif into each basic form. Thirdly, fill colour on the background.